Cross-reacting surface proteins between different Escherichia coli O157:H7 strains and their immune responses in animal models - Nabi, Ashikun; Chowdhury, Fatema Moni; Jahan, Zeenat; Sarkar, Md Murshed Hasan; Rabbi, Fazle; Ahsan, Chowdhury Rafiqul (Bangladesh Journal of Microbiology, 2019)
Surface proteins of Escherichia coli O157:H7, those that are prominent in antigen-antibody reactions among different strains, were found to provide protection against E. coli O157 challenge in mice. Three strains such as E. coli O157:H7 NCTC reference strain and two other environmentally isolated strains have been used in this study. New Zealand rabbits were immunized with surface proteins of NCTC reference strain and immunoblot analysis was performed against the surface proteins of all three strains. Immunoblot analysis revealed that a 94 kDa surface protein of E. coli O157:H7 could be the possible candidate for the protective activity experiment. Group of mice receiving the 94 kDa surface protein through both intraperitoneal and intranasal routes survived the challenge experiment. Whereas, all the control mice died within a couple of days. Mice challenge experiment clearly demonstrated the strong potential of the 94 kDa protein in the immunized mice. The data of this study provide us with a basis for further characterization of 94 kDa surface protein of E. coli O157:H7 as a protective antigen. Bangladesh J Microbiol, Volume 36 Number 1 June 2019, pp 11-15